3D-printed resin composite posterior fixed dental prosthesis: a prospective clinical trial up to 1 year - Hobbi, Paniz; Ordueri, Tugce Merve; Öztürk-Bozkurt, Funda; Toz-Akalın, Tugba; Ateş, Muzaffer; Özcan, Mutlu (Frontiers in Dental Medicine, 2024)
Objectives This clinical trial evaluated the clinical behavior of 3D-printed posterior resin composite fixed dental prostheses (FDPs). Materials and methods Between 10 October 2020 and 5 August 2022, 49 patients aged 19–60 years (16 men, 33 women) received 68 3D-printed resin composite 3-unit posterior FDPs (ELS Even Stronger, Saremco, Switzerland). FDPs were followed up 2 weeks after placement (baseline), 6 months after placement, and 1 year after placement by two independent calibrated observers using modified FDI criteria for anatomical form, secondary caries, marginal adaptation, surface roughness, color match, fracture of material, staining surface, staining margin, approximate anatomical form, retention, gingival health, and patient's view. Survival analyses were performed using Kaplan–Meier analyses. Results A total of 59 restorations were evaluated and the mean observation period was 8.63 months. Failure types were categorized as mechanical and biological. Failures were observed in 14 FDPs. Nine FDPs showed mechanical failure and five FDPs showed biological failure. Mechanical failures were mostly experienced as connector fractures. Eight FDPs showed cohesive fractures (seven in a single connector at either at the mesial or distal and one in the pontic itself). Biological failures, including root canal treatment and gingival tissue reactions, were observed within the first 6 months. Based on mechanical failures, the survival rate was 86.7% including the biological complications; this corresponded to 71.6% (Kaplan–Meier). After 1 year, two FDPs showed surface luster loss (score 4), two-color mismatches (score 4), and two-surface staining (score 4). Conclusion 3D-printed resin composite FDPs were observed acceptable after 1 year of clinical follow-up, providing that the experienced failure types were mainly associated with fractures in the connector region, which requires revision of design parameters. Clinical Trial Registration Clinical Trials.Gov, NCT04600297.